ASTROFOTOGRAFI DALAM RUKYATUL HILAL PERSPEKTIF HUKUM ISLAM - Syamsuddin, Nuramaliah; Muh. Akmal, Andi (HISABUNA: Jurnal Ilmu Falak, 2024)
This research is entitled astrophotography in the rukyatul hilal perspective of Islamic law. The focus of this research is the concept of astrophotography in rukyatul hilal, the implementation of astrophotography in Islamic law and the analysis of Islamic law on the results of astrophotography. The aim of this research is to find out the concept of astrophotography in rukyatul hilal, the implementation of astrophotography in Islamic law and the analysis of Islamic law on the results of astrophotography. The type of research used by researchers in this article is literature review sourced from books, journals, theses and other scientific studies that are relevant to the research object. The results of the research in this article are that rukyatul hilal is a method of viewing the moon to determine the beginning of the month of Qamariyah, astrophotography is a tool for making these observations. The implementation of astrophography is a way to make it easier to observe the rukyatul hilal using tools. Analysis of Islamic law related to astrophotography is carried out using an approach through maslahah murlah and fiqh rules related to the implementation of astrophotography. It is hoped that the implications of this research will lead to the study of astronomy, especially in terms of rukyah hilal and astrophotography.